2019
DOI: 10.1002/smll.201902920
|View full text |Cite
|
Sign up to set email alerts
|

High Spatial Resolution Mapping of Localized Surface Plasmon Resonances in Single Gallium Nanoparticles

Abstract: materials, as certain semiconductor systems, [6] have been demonstrated to show plasmonic behavior, where the plasmon resonance is achieved by the excitation of interband transitions. [7] Among metals, noble metals as gold and silver have been the most extensively studied and exploited plasmonic systems, whose response lies on the VIS-IR spectral region. However, expanding the operability range up to the UV region is highly desirable to cover further applications, [8] which requires exploring alternative plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…This two cases lead to aspect ratios of 0.7 and 0.71. Those values are compatible to have two different separated resonances as previously confirmed with EELS measurements 59 and strengthen our premise that the LSPR band around 200-400 nm in Fig. 2(f) corresponds to an out-of-plane resonant mode.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This two cases lead to aspect ratios of 0.7 and 0.71. Those values are compatible to have two different separated resonances as previously confirmed with EELS measurements 59 and strengthen our premise that the LSPR band around 200-400 nm in Fig. 2(f) corresponds to an out-of-plane resonant mode.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the main band for each Ga mass presents at higher energies a shoulder that is likely due to higher order resonance modes such as quadrupoles based on the similarity of the NP sizes and the light wavelength in all the cases. In fact, similar Ga NP diameters have been demonstrated to support dipoles and quadrupoles modes simultaneously as evidenced by electron energy loss spectroscopy (EELS) measurements 58 . However, apart from the main band, a lower intensity bands around 200-400 nm also exist.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, in contrast to UV-Vis spectroscopy, EELS provides near-field measurements upon electron excitation. Moreover, the extraordinary combination of spatial and spectral resolution attainable by STEM allows 2D 32,33 and 3D 22,34 single particle studies (maps and tomographic reconstructions), higher-order multipole excitation and the ability of probing dark resonant modes as well as bright modes 22,35 . Consequently, plasmonic NPs have been broadly studied by means of EELS over the last years 28 , including substrate supported systems 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the low melting temperature of gallium allows low-temperature fabrication with low energy consumption. Prior studies reported plasmonic properties of gallium nanoparticles, , tuning of the plasmon resonance by oxidation creating Ga–Ga 2 O 3 core–shell structures that were further studied in detail, including their thermal stability, gallium–indium alloy nanoparticles, and silver–gallium alloy nanoparticles . There are numerous applications for such nanoparticles.…”
mentioning
confidence: 99%
“…Only two experimental studies have focused on the optical properties of individual gallium nanoparticles. These studies utilized either electron energy loss spectroscopy or cathodoluminescence . Here, we present a study combining electron energy loss spectroscopy in a scanning transmission electron microscope (STEM-EELS) and numerical simulations to address the optical response of individual gallium nanoparticles.…”
mentioning
confidence: 99%